Family center maternity care education for pregnant women through the approachin efforts to prevent stunting: a quasi-experimental - Irne Wida Desiyanti; Lisa Ardiningtyas (Medisains)
Background: Stunting in children is a health problem that has a great influence on their physical and mental development. In Indonesia, one of the causes of high stunting rates is the low health awareness of pregnant women, especially those who marry at a young age. Family factors have a significant influence on the success of stunting prevention, but family-based approaches are still rarely applied in pregnant women's health education programs.